Strategi Promotion Mix Untuk Peningkatan Penjualan UMKM Pada Katering Abg Rafin Percut Sei Tuan - Anggraini, Nur Marliana; Ramadhan, Muhammad; Harahap, Muhammad Ikhsan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to analyze and formulate an effective promotion mix strategy to increase sales in Abg Rafin Catering's Micro, Small, and Medium Enterprises (UMKM) located in Percut Sei Tuan. Abg Raffin Catering has been operating for several years and has a loyal customer base. As UMKM operates in the culinary sector, Katering Abg Rafin faces the challenge of increasing market share and revenue amidst tight competition. And in recent years, sales growth has stagnated. One factor contributing to this problem is the lack of optimality in the promotion strategy used. Many UMKMs, including Abg Rafin's Catering, tend to rely on traditional promotion methods, which are now becoming less competitive with digital marketing techniques and more modern promotion approaches. To achieve that goal, a proper promotion mix strategy is essential. We use qualitative research with case study methods. Data is collected through in-depth interviews with business owners, customer surveys, as well as analysis of sales and promotional documents. The results show that an optimal combination of the components of the promotion mix—advertising, direct marketing, personal selling, sales promotion, and publicity—can significantly increase sales. In particular, the increased use of social media and digital platforms as a means of promotion has had the greatest impact. Based on the findings, it is recommended that Katering Abg Rafin implement an integrated and sustainable promotion mix strategy, focusing on enhanced digital marketing activities and direct interaction with customers. This approach is expected to help Katering Abg Rafin compete more effectively in the market and sustain sales growth.